(untitled) (World Bulletin of Public Health, 2023)
In parallel with clinical, anamnestic and instrumental studies, to study the functional state of the digestive-transport conveyor of the SI, by simultaneously determining the activity of enzymes involved in cavity, membrane hydrolysis and absorption of carbohydrates in patients with gastroduodenal bleeding (GDB) of varying severity